History and catalogue of reptile types in the collection of the Zoological Survey of India - Das, I.; Basudeb, Dattagupta; Nimai Charan, Gayen (Wildlife Heritage Trust of Sri Lanka, 1998)
The contents of the reptile type collection of the Zoological Survey of India, headquartered in Calcutta, with several regional stations in the country, which incorporates the holdings of the Asiatic Society of Bengal and the Indian Museum, are listed. The annotated list includes original citations, registration numbers, nature of type and present status of every taxon, with additional remarks where necessary. In all, 556 primary and secondary types are present, including 289 name-bearing types (comprising 27 Chelonii, 152 Sauria and 110 Serpentes). A list of types that were not located, including those erroneously mentioned as being in the collection, is also included.